(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Road traffic accident (RTAs) refer to fatal or nonfatal injuries caused by the collision of at least one moving vehicle on a public road. At present, RTIs are the eighth leading cause of death in the world and the fifth leading cause of reduced life expectancy and have been a persistent problem that the Chinese government is committed to dealing with. The aim of this study was to assess the causes and complication of road traffic accident in Mosul city. Material and methods: The questionnaire consisted of three parts, the first includes (the demographic characteristics of the accident victims), the second includes (the characteristics of the accident), and the third part includes (the nature of the injuries). A non-probability convenience sample of (78) accident victims was recruited from the emergency departments of Al-Salam and Aljumhoory Hospitals for the period from 1st January 1st to February, 2023.Data were collected through direct interview with the victims or their relatives follows the authority of Nineveh Health Director. Result: The study find out the Speed was identified as the leading cause of accidents, accounting for 28.2% of the cases.Other significant causes included inattention (28.2%), the road conditions (21.8%), and the weather (9.0%).Phone use, traffic safety, and other factors contributed to a smaller percentage of accidents.. Conclusion: The study concludes that Speed was identified as the leading cause of accidents, accounting for 28.2% of the cases, and the study found that the rate of death about one quarter (23.1 %) of the victims. Recommendation: The study recommended proposals that could be submitted to the Ministry of Education, and the Ministry of Higher Education, to hold awareness seminars for secondary school students and universities for educate about the dangers of roads accidents to reduce them.